The role of social network analysis on participation and placemaking - Alvarez, Laura; Borsi, Katharina; Rodrigues, Lucélia Taranto (Elsevier, 2017)
Social networks give structure to our world, are key to building social capital and can form a platform to build-up strength and ability to change; they are, however, often absent from urban studies. In this paper, the authors explored the potential role of social networks during community consultations, both as an engagement tool and as a mechanism for capturing existing placemaking dynamics in neighbourhoods.